STRATEGIES INFLUENCING ARTIFICIAL INTELLIGENCE (AI) ADOPTION AMONG ACCOUNTING PERSONNEL IN MALAYSIA: A FUZZY DELPHI ANALYSIS - Cha, Norlela Awang; Mohamad, Zam Zuriyati; Zakaria, Zuriawati (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2026)
Purpose. Artificial Intelligence (AI) has become increasingly important in transforming accounting practices through automation, predictive analytics, intelligent auditing systems, and cloud accounting technologies. Despite rapid technological development and government initiatives to encourage digital transformation, the adoption of AI among accounting personnel in Malaysia remains relatively low. Therefore, this study aims to identify the important strategies influencing AI adoption among accounting personnel in Malaysia. Problem statement. Accounting personnel remain reluctant to adopt the technology, despite many campaigns and awareness have been carried out by the companies and government. The hesitation to adopt AI because of lack of knowledge, concern about security and confidentiality, lack of trust and the strong preference for using traditional methods to complete the accounting tasks. Furthermore, the function and application of AI are very complex and costly. Small accounting businesses are unable to adopt AI due to insufficient funds and limited awareness of AI adoption. Methodology. This study focuses on strategies for AI adoption among accounting personnel in Malaysia using the Fuzzy Delphi method. A total of 15 accounting experts were selected as respondents, of which 5 were from academia and 10 were from industry. There are 5 aspects and 26 criteria proposed in this study. Findings: The results showed that only 4 aspects and 13 criteria were accepted at a threshold of 0.44 for aspects as well as criteria. The findings revealed that support from government, vendors, and management, responsible AI development, cost effectiveness, and accelerated AI adoption were identified as the most important factors influencing AI adoption among accounting personnel in Malaysia. Implications: The study contributes to the literature by providing expert consensus regarding strategic factors influencing AI adoption among accounting personnel. The findings also provide practical implications for policymakers, professional accounting bodies, and organizations in developing effective AI adoption strategies.